The prompt use of rituximab could decrease adverse effects in patient with pemphigus vulgaris: A preliminary evaluation. (23rd December 2019) - Arduino, Paolo G.; Broccoletti, Roberto; Carbone, Mario; Conrotto, Davide; Sciannameo, Veronica; Gambino, Alessio; Cabras, Marco; Carrozzo, Marco; Baldovino, Simone
Abstract: Background: The systemic use of corticosteroid is the treatment of choice for patients with pemphigus vulgaris (PV), but adverse effects are frequent. To date, the use of rituximab (RTX) for PV patients is usually indicated when they failed first‐line immunosuppressive therapies. The early use of RTX could theoretically lessen adverse effects. Methods: We performed a single‐center study on patients with predominantly oral PV, treated with systemic corticosteroid and the prompt use of 1000 mg of intravenous RTX two weeks apart. We evaluated the clinical response and the reported adverse effect during a period of 24 months, comparing those with a previously published series. Results: The study group comprised 11 patients, while the control group comprised 98 patients. The average time to achieve complete clinical remission was 3.2 ± 2.72 months. Study group took steroids for a mean time of 11.09 ± 2.02 months, and they are all actually disease‐free with no medication. Only three patients (27.3%) developed plain side effects. The effect of the length of the corticosteroid therapy on the side effects (also adjusted by sex, age, and clinical oral involvement) was statistically different in the two groups: the prompt use of RTX reduced of 94% the chance to have adverse effects ( P = .001). Conclusions: This is the first report of the use of RTX as first line of therapy for PV patients with predominantly oral involvement. With the proposed regimen, the adverse effects have been minimized compared with classic systemic corticosteroid‐centered therapy. Multi‐center randomized controlled trail is however necessary.